The Influence of Celebrity Endorser and Brand Image on Erigo Purchase Decisions in Surabaya - Calvin Rajagukguk; Ugy Soebiantoro (Universitas KH. Abdul Chalim Mojokerto, 2024)
This research aims to explore the influence of celebrity endorsers and brand image on Erigo's purchasing decisions in the city of Surabaya. In this case, celebrity endorsers and brand image are considered important in increasing purchasing decisions for a product. This research uses a qualitative method using a questionnaire which is used to collect data and the population in this research is the people of Surabaya who have purchased Erigo products with a sample of 90 respondents. Data analysis uses the Partial Least Square (PLS) method. Celebrity endorsers have the most influential indicator, namely power, and brand image has the most influential indicator, product image. The research results show that celebrity endorsers have a positive and significant influence on the decision to purchase Erigo products in the city of Surabaya as well as the brand image has a positive and significant influence on the decision to purchase Erigo products in the city of Surabaya. These findings show that there is a relationship that mutually influences celebrity endorsers, brand image, and Erigo purchasing decisions in the city of Surabaya.